Α–ω Alkenyl‐bis‐S‐Guanidine Thiourea Dihydrobromide Affects HeLa Cell Growth Hampering Tubulin Polymerization. (18th September 2020) - Ceramella, Jessica; Mariconda, Annaluisa; Rosano, Camillo; Iacopetta, Domenico; Caruso, Anna; Longo, Pasquale; Sinicropi, Maria Stefania; Saturnino, Carmela
Abstract: Cancer is going to be the first cause of mortality worldwide in the 21th century. It is considered a multifactorial disease that results from the combined influence of many genetic aberrations, leading to abnormal cell proliferation. As microtubules are strongly implicated in cellular growth, they represent an important target for cancer treatment. The well‐known microtubule‐targeting agents (MTAs) including paclitaxel, colchicine and vinca alkaloids are commonly used in the treatment of various cancers. However, adverse effects and drug resistance are major limitations in their clinical use. To find new candidates able to induce microtubule alteration with reduced toxic effects or drug resistance, we studied a small new series of derivatives that present imidazolinic, guanidinic, thioureidic and hydrazinic groups (1 –9 ). All the compounds were tested for their antitumor activity against a panel of six tumoral cell models. In particular, compound 8 (nonane‐1, 9‐diyl‐bis‐ S ‐amidinothiourea dihydrobromide) showed the lowest IC50 value against HeLa cells, together with a low cytotoxicity for normal cells. This compound was able to induce the apoptotic mitochondrial pathway and inhibited tubulin polymerization with a similar efficacy to vinblastine and nocodazole. Taken together, these promising biological properties make compound 8 useful for the development of novel therapeutic approaches in cancer treatment. Abstract : Active and specific : The newly synthesized compound 8 (nonane‐1, 9‐diyl‐bis‐ S ‐amidinothiourea dihydrobromide) affects HeLa cell growth by targeting tubulin polymerization and inducing Parp‐1 cleavage and cytochrome  c release from mitochondria, the hallmarks of the intrinsic apoptotic pathway.